2004
DOI: 10.1002/crat.200310238
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization kinetics of ZnS precipitation; an experimental study using the mixed‐suspension‐mixed‐product‐removal (MSMPR) method

Abstract: The precipitation kinetics of zinc sulfide were studied using a lab scale mixed-suspension-mixed-productremoval (MSMPR) precipitation reactor. The vessel was operated at different feed concentrations, molar ratios, stirrer speeds, pH-values, feed injection positions and residence times. Primary nucleation and volume average crystal growth rates as well as agglomeration kernel were determined. Relationships were found between the rates of the different crystallization steps on the one hand and supersaturation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 10 publications
3
33
0
1
Order By: Relevance
“…The PSD analysis showed that bigger particles were formed at lower supersaturation levels (higher pS), which is in accordance with previous studies [44][45][46]. Moreover, such particles are very sensitive to the hydraulic conditions applied, indicating that rather than crystal growth, enlargement due to agglomeration should be the ruling process on the formation of the ∼30 m particles.…”
Section: Solid Phase Characterizationsupporting
confidence: 86%
See 1 more Smart Citation
“…The PSD analysis showed that bigger particles were formed at lower supersaturation levels (higher pS), which is in accordance with previous studies [44][45][46]. Moreover, such particles are very sensitive to the hydraulic conditions applied, indicating that rather than crystal growth, enlargement due to agglomeration should be the ruling process on the formation of the ∼30 m particles.…”
Section: Solid Phase Characterizationsupporting
confidence: 86%
“…Moreover, such particles are very sensitive to the hydraulic conditions applied, indicating that rather than crystal growth, enlargement due to agglomeration should be the ruling process on the formation of the ∼30 m particles. In the literature, several examples reporting the importance of the agglomeration phenomena in the case of very fast precipitations and supersaturated solutions are given [44,[47][48][49]. As metal sulfides have very low solubility products and fast reaction kinetics, high levels of supersaturation cannot be avoided [50].…”
Section: Solid Phase Characterizationmentioning
confidence: 98%
“…Precipitation occurs through several steps: nucleation, crystal growth, and eventually agglomeration [30]. Large particles can be produced if the supersaturation is optimum to promote crystal growth, and the residence time of the crystals is long enough to promote agglomeration [31].…”
Section: Effect Of Agglomerationmentioning
confidence: 99%
“…The morphologies of agglomerates of ZnSe nanoparticles depended markedly on the pH values in the reactor (and therefore on the amount of hydrazine hydrate added). Crystallization kinetics (primary nucleation, crystal growth, and agglomeration) of ZnSe depended on supersaturation, stirrer speed, pH, molar feed ratio and residence time [34]. It is very difficult to estimate the relationship between agglomeration and crystal growth kinetics [35].…”
Section: Effect Of Ph On Particle Size and Morphologiesmentioning
confidence: 99%